(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Cesarean delivery is one of the most performed surgical procedures worldwide and is associated with significant postoperative morbidity, including pain, delayed mobilization, prolonged hospital stays, and increased opioid use. Enhanced Recovery After Cesarean (ERAC) protocols, adapted from Enhanced Recovery After Surgery (ERAS) principles, have been developed to optimize perioperative care and improve maternal recovery. However, variability in implementation and outcomes necessitates a comprehensive synthesis of the available evidence. Objective: To systematically review and evaluate the effectiveness of enhanced recovery after cesarean delivery (ERAC) protocols in improving postoperative maternal outcomes and overall quality of recovery compared with conventional postoperative care. Methods: A systematic literature search was conducted across multiple electronic databases, including PubMed/MEDLINE, Web of Science and research gate from inception to the most recent search date. Eligible studies included randomized controlled trials and observational studies evaluating ERAC protocols in women undergoing cesarean delivery. Primary outcomes included length of hospital stay, postoperative pain scores and postoperative complications. Secondary outcomes included maternal satisfaction, breastfeeding outcomes, readmission rates, and neonatal safety. Study selection and data extraction were performed independently by 3 of the authors. Results: The included studies consistently demonstrated that implementation of ERAC protocols was associated with shorter hospital stay, earlier mobilization, and improved postoperative pain control compared with standard care. Several studies also reported higher maternal satisfaction and earlier initiation of breastfeeding without an increase in maternal or neonatal complications. Hence, the overall direction of evidence favored ERAC implementation. Conclusion: Enhanced recovery after cesarean delivery protocols appears to be safe and effective in improving postoperative maternal recovery and reducing healthcare resource utilization. Standardization of ERAC components and broader implementation may enhance post-cesarean care outcomes. Further high-quality randomized trials are needed to establish optimal protocol elements and assess long-term maternal and neonatal outcomes.